Prevalence of Obesity and Physical Activity among Individuals at Umm Al-Qura University - M. Altowerqi , zayed (Journal of Physical Education, 2025)
To assess the prevalence of obesity and physical activity among individuals at Umm Al Qura University, a cross-sectional study design was applied from January to August 2024. Data collection was conducted through a questionnaire titled "Prevalence of Body Mass Index and Physical Activity in University Individuals" administered at Umm Al-Qura University. Participants completed an online, self-administered questionnaire that gathered information on sports participation, age, height, and weight. The results of this study showed that 23.2% of the participants were overweight and 16.7% were obese. Specifically, 11.59% of male were obese and 14.21% were overweight. Among females, 8.9% were overweight, and 5.10% were obese. Regarding physical activity 47.2% did not engage in any form of physical activity. Among those inactive, 21.10% were male, and 26.7% were female. Additionally, 12% of overweight and 8.55% of obese individuals reported no participation in any physical activity. This study will help in creating awareness among university people to adopt a healthy lifestyle.